2018
DOI: 10.1007/s00784-018-2442-x
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of surgical drain placement and the use of kinesiologic tape to reduce postoperative morbidity after third molar surgery

Abstract: Although both treatments were useful, a surgical drain was significantly more effective at reducing swelling and pain intensity than Kinesio tape. The effects of both on trismus were similar.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 16 publications
3
30
0
Order By: Relevance
“…Postoperative swelling, pain, and limitation of mouth opening are common after impacted third molar surgeries and severely decrease the patients’ quality of life. Despite the increased clinical application of KT in physiotherapy practice, especially after traumatic injuries, only a few studies investigate the effectiveness of KT in OMS literature; two studies showing effects of KT after maxillofacial trauma, 17 , 19 four studies after impacted tooth surgery, 5 , 15 , 16 , 18 two studies after orthognathic surgery, 20 , 21 and one study for temporomandibular joint disorders. 23 However, the aforementioned studies did not include placebo taping.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Postoperative swelling, pain, and limitation of mouth opening are common after impacted third molar surgeries and severely decrease the patients’ quality of life. Despite the increased clinical application of KT in physiotherapy practice, especially after traumatic injuries, only a few studies investigate the effectiveness of KT in OMS literature; two studies showing effects of KT after maxillofacial trauma, 17 , 19 four studies after impacted tooth surgery, 5 , 15 , 16 , 18 two studies after orthognathic surgery, 20 , 21 and one study for temporomandibular joint disorders. 23 However, the aforementioned studies did not include placebo taping.…”
Section: Discussionmentioning
confidence: 99%
“…A recent split-mouth clinical study by Gözlüklü, et al 16 (2020) reported that their newly described KT method was more effective when compared with classic KT method in reducing postoperative morbidity after impacted third molar surgery. Genc, et al 5 (2019) compared the effectiveness of KT and surgical drain on postoperative morbidity after third molar surgery, observing significantly greater swelling and pain in KT group, and comparable occurrence of trismus in both groups. Lietz-Kijak, et al 21 (2018) revealed that KT had beneficial effects on the reduction of facial swelling after orthognathic surgery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite this, none of the treatments helped reduce trismus in this study. It should also be considered that drainage placement, despite being effective in reducing edema, may lead to other complications, in relation to the possibility of subcutaneous emphysema, infection, and external facial scar [98].…”
Section: Kinesio Taping (Kt)mentioning
confidence: 99%